Starting Out in Project Management : a study guide for the APM introductory certificate in project management - Murray-Webster, Ruth; Simon, Peter (Buckinghamshire, UK : Association for Project Management &#x000A, 2007)
Starting Out in Project Management is a very detailed and meticulously crafted study guide that will support readers wishing to take APM Introductory Certificate in Project Management examination. It provides close and direct support for the APM syllabus.
Includes index.
oif 18/06/14
Loan
Keywords: Project management